Notes of a Radiology Watcher - Baker, Stephen R. (Springer International Publishing : Imprint: Springer, 2014)
Written by an expert in the field, Notes of a Radiology Watcher presents a compilation of essays given by the author, which run from clinical issues to practical matters, from residency concerns to ruminations about the future of radiology and about comparisons between U.S. radiology and diagnostic imaging practice abroad.   Notes of a Radiology Watcher aims to show the reader how radiology is being transformed from its customary focus of the last 40 years to meet the disparate challenges of competing influences and an uncertain future. Considerations on the elaboration of 'milestones' for residency education are examined, as well as the social and economic issues that are codified into focused initiatives that must be addressed by each trainee as they advance in capability and seniority within the training interval. With the expanse and reorganization schemes of training of the Accreditation Committee for the Graduate Medical Education (ACGME), this book is of interest to radiologists worldwide as it discusses both the U.S. models of training as well as foreign national health models, new initiatives and quality issues.